AS PRÁTICAS PEDAGÓGICAS NO CONTEXTO SOCIOEDUCATIVO - Lopes, Henrique Corrêa (2022)
This study aims to analyze and reflect on the pedagogical practices applied in a unit of the Centro de Atendimento Socioeducativo (CASE) in the city of Santa Maria - RS, presenting some of the pedagogical difficulties experienced in the educational context inserted in a service unit for adolescents in socio-educational measure. The importance of teacher training and pedagogical practices are constantly related to an innovative education that can use new teaching methodologies or pedagogical practices. In this context, related to the external school network, this work brings the possibility of inserting pedagogical activities used in traditional schools, that is, external schools, with a bias towards inclusive education and the use of materials related to information technology for adolescents hospitalized in a socio-educational service unit in compliance with the socio-educational measure. This study has a qualitative approach, and its investigation is based on action research, due to its constant modification during research and practice. As a theoretical reference, authors Freire (1996, 2018, 2020, 2021) and Romanowski (2012) are cited with the approach to the pedagogy of education, about teaching practices such as Kraviski (2020) and Santos (2020) on the restorative practices. In this study, aspects of teaching practices and pedagogical actions that could be applied in the school inserted in the socio educational service institution were verified, with the possibility of creating new pedagogical activities, also called internally in the school of workshops. In this way, the emotional and motivational factors that influence the educator's work in the care of young people in the socio-educational system and relating the teaching dynamics and the possibility of developing different pedagogical activities, provided adolescents with the attributes for the exercise of citizenship and their reintegration social.